Determinants of Fruits and Vegetables Consumption among In-School Adolescents in Ghana - Abdul-Aziz Seidu; Richard Gyan Aboagye; James Boadu Frimpong; Hawa Iddrisu; Ebenezer Agbaglo; Eugene Budu; John Elvis Hagan; Bright Opoku Ahinkorah (MDPI AG, 2021)
Background: Fruit and vegetable consumption is an important source of nutrients for healthy growth and development, as well as a protective factor against chronic non-communicable diseases. Paucity of data exists on adolescents' fruit and vegetable consumption in Ghana. This study, therefore, sought to determine the prevalence and correlates of fruit and vegetable consumption among in-school adolescents in Ghana. Methods: Data for this study were extracted from the 2012 Global School-Based Health Survey. A cross-sectional analysis on 2786 in-school adolescents from junior and senior high schools was conducted. Descriptive analyses using frequencies and percentages were used to present the results on the prevalence of fruit and vegetable consumption. Multivariable binomial regression analysis was performed to determine the association between fruit and vegetable consumption and explanatory variables. The results of the regression analyses were presented using adjusted odds ratio (aOR) with their respective confidence intervals (CIs). Statistical significance was set at p < 0.05. Results: The prevalence of adequate fruits, adequate vegetables, and adequate fruit and vegetable consumption were 35.7%, 26.8%, and 27.8%, respectively. In-school male adolescents had lower odds of adequate fruit and vegetable consumption compared to female adolescents (aOR = 0.64, 95%CI = 0.51-0.82). Adolescents in senior high schools (aOR = 0.36, 95%CI = 0.22-0.61) were less likely to consume adequate fruits and vegetables compared to those in junior high schools. The odds of adequate fruit and vegetable consumption were higher among adolescents who consumed soft drinks (aOR = 3.29, 95%CI = 2.42-4.46), fast foods (aOR = 1.42, 95%CI = 1.13-1.77), and those who had sedentary behavior (aOR = 1.38, 95%CI = 1.07-1.77). Conclusions: The findings revealed that fruit and vegetable consumption among Ghanaian adolescents is relatively low. Sex of adolescents, grade, soft drink intake, fast food consumption, and sedentary behavior were factors associated with adequate fruit and vegetable consumption. Health promotion interventions to scale up fruit and vegetable consumption should pay attention to the factors identified in this study.